1998
DOI: 10.1016/s0735-1097(98)00213-7
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac sympathetic innervation in patients with idiopathic right ventricular outflow tract tachycardia

Abstract: The findings of the present study suggest that myocardial beta-adrenoceptor downregulation in patients with RVO-VT occurs subsequently to increased local synaptic catecholamine levels caused by impaired catecholamine reuptake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
1
5

Year Published

2004
2004
2019
2019

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 91 publications
(52 citation statements)
references
References 26 publications
1
43
1
5
Order By: Relevance
“…12 Studies using positron emission tomography (PET) with 11 C-hydroxyephedrine ( 11 C-HED) and 11 C-CGP (CibaGeigy product) 12177 have shown that both ARVC and RVO-VT were characterized by reduced presynaptic catecholamine recycling and downregulation of postsynaptic ␤-adrenoceptors. 13,14 In the present study, we aimed to further investigate and prove our previous observations made with SPECT and 123 I-MIBG in patients with Brugada syndrome by noninvasive quantification of myocardial presynaptic and postsynaptic sympathetic function, using PET with 11 C-HED and 11 C-CGP. The results in patients were compared with those obtained in 2 groups of age-matched normal volunteers.…”
mentioning
confidence: 83%
See 3 more Smart Citations
“…12 Studies using positron emission tomography (PET) with 11 C-hydroxyephedrine ( 11 C-HED) and 11 C-CGP (CibaGeigy product) 12177 have shown that both ARVC and RVO-VT were characterized by reduced presynaptic catecholamine recycling and downregulation of postsynaptic ␤-adrenoceptors. 13,14 In the present study, we aimed to further investigate and prove our previous observations made with SPECT and 123 I-MIBG in patients with Brugada syndrome by noninvasive quantification of myocardial presynaptic and postsynaptic sympathetic function, using PET with 11 C-HED and 11 C-CGP. The results in patients were compared with those obtained in 2 groups of age-matched normal volunteers.…”
mentioning
confidence: 83%
“…13,14,19 Presynaptic Norepinephrine Recycling 11 C-HED was prepared and infused intravenously as described previously. 13 ing the volume of distribution (V d ) of 11 C-HED with the use of a single-tissue compartment model.…”
Section: Pet Data Acquisition and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Mitrani et al 128 observed that in patients who presented with VT but had structurally normal hearts, 55% had regional sympathetic denervation compared with none of the control patients. Gill et al 129 found asymmetrical uptake of 123 ImIBG (less in septum) in 47% of patients with VT and ''clinically normal'' hearts, particularly obvious in patients with exercise-induced VT. Interestingly, PET autonomic tracer (i.e., 11 C-HED) imaging of particular primary arrhythmias, such as right ventricular outflow tract tachycardia 130 and Brugada syndrome, shows focal defects in specific myocardial walls. 131 Regional autonomic abnormalities can also be seen in nonischemic cardiomyopathies, such as Chagas disease in which the posterolateral, inferior, and apical walls are selectively affected.…”
Section: Cardiac Arrhythmiasmentioning
confidence: 99%